فاعلية برنامج ارشادي مقترح مبنى على اللعب في خفض الاندفاعية و رفع الانتباه لدى عينة من التلاميذ مفرطي النشاط مشتتي الانتباه - بن مجغاية عفاف; تريش حورية; بدوي عائشة (My University, 2021)
Our current study aims to reveal the effect of the playing program on hyperactivity and attention deficit among fourth-year students at the Muhaigira Abdelkader Primary School, in Laghouat. And that is by identifying the hyperactivity and distraction of the sample members and identifying the play programs and their importance in education. And the answer to the problem of the study, which is, is there an effect of playing programs on the hyperactivity and distraction of the fourth year students at the Primary School, Muhaigira Abdelkader in Laghouat? We conducted the field study based on the following assumptions: There are differences between the pre-measurement and the post-measurement in the level of attention deficit hyperactivity disorder. There are differences between the post-measurement and the trace-measurement in the level of attention deficit hyperactivity disorder. In order to answer these hypotheses, we conducted a field study according to the experimental method, where we conducted a set of tests (pre-, post-, follow-up) on a group of students of the fourth year of primary school in Muhaigira Abdelkader in Laghouat. We also distributed a questionnaire on the level of students' attention deficit hyperactivity disorder from the point of view of primary school teachers. To conclude, in the end, that there is an effect of playing programs on hyperactivity and attention-deficit among students of the fourth year of primary school at Muhaigira Abdelkader in Laghouat. gaming programs, hyperactivity, distraction.